JAEPL, Vol. 15, Winter 2009-2010 - Kristie S. Fleckenstein; Linda T. Calendrillo (Journal of the Assembly for Expanded Perspectives on Learning, 2009)
Essays Peter Elbow - Reflections from a Grateful Guest Editor Sheridan Blau - Believing and Doubting as Hermeneutic Metbod: Reading and Teaching Paradue Lost Tim Doherty - Lessons from tbe Believing Game Anne Ellen Geller - The Difficulty of Believing in Writing Across the Curriculum Shelly Sheats Harkness, Catherine Pullin Lane, Sue Mau, Amber Brass - The Believing Game in Mathematics: Stories in a Discipline of Doubt Judy Lightfoot - Saying Yes to Freestyle Volunteering: Doubting and Believing Clyde Moneyhun - Believing, Doubting, Deciding, Acting Irene Papoulis - A Refiection on Habitual Belief and Habitual Doubt Stephanie Paterson - Friday Writes: An Exercise in the Believing Game Donna Strickland - Before Belief: Embodiment and the "Trying Game" Peter Elbow - A Highly Incomplete Bibliography Reviews Julie J. Nichols - Meaning and The Evolution of Consciousness: A Retrospective on the Writing of Owen Barfield Charles Suhor - The Great Transfonnation: The Beginnings of Our Religious Traditions Charles Suhor - The Chalice and the Blade Edward Sullivan - The Art of Learning: An Inner Journey to Optimal Performance Connecting - Helen Walker Andrew Statum - The Question Vic Kryston -Conflict Resolution Jie Li - Teaching with Accent Dominique Zino - Space Joonna Smitherman Trapp - Composition Class 7:45 AM